Prevalence and Associated Risk Factors of Hypertension among Pregnant Women in Rural Areas of South Punjab - Anwish Ali, Uzma Arshad, Shehlla Qadir, Ayesha Saddique, Laiba Ishaq, Abeer Zahra (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hypertension is a frequently encountered medical condition that can arise during pregnancies, affecting a significant proportion of expectant mothers, ranging from 4% to 9.5% of all pregnancies. Objective: To calculate the prevalence of hypertension in pregnant women in rural areas of South Punjab, Pakistan, and identify the obstetric risk factors linked with hypertension in them. Settings and Design: A Cohort Study was conducted at Multan Medical and Dental College, Multan. Materials and Methods: Pregnant women in two health block villages were the subjects of the current study, which ran from May 2020 to April 2021. A sample size of 765 was determined. Pregnant women predicted to be in each block were recorded, and proportionate allocation was used to determine which pregnant women from each block and sub-center would be included. The villages in each sub-center were surveyed house to home to gather data. The data was gathered using a proforma that had been previously created and tested. Data was analyzed using Results analyzed from SPSS 24. Results: 765 pregnant women in all gave their permission to participate. Pregnancy-related hypertension was 10.2% prevalent. The following obstetric characteristics were statistically significant risk factors for hypertension in pregnancy: multigravidity, multiparity, gestational age greater than 24 weeks, history of hypertension in a previous pregnancy, and history of stillbirth. Maternal hypertension was found to be independently predicted by gestational age longer than 24 weeks, according to a logistic regression study. Conclusion: Understanding the obstetric risk factors associated with pregnancy-related hypertension may help preventative measures for this population. Keywords: Pregnant women, hypertension, rural areas.